Characterizing host genetic resistance to Wheat streak mosaic virus (WSMV) and Fusarium wilt disease - Xie, Yucong, author; Pearce, Stephen, advisor; Argueso, Cristiana, committee member; Muñoz-Amatriaín, María, committee member; Nachappa, Punya, committee member (Colorado State University. Libraries, 2021)
Crop production is limited by a variety of biotic stresses caused by pathogens. This study focuses on wheat streak mosaic disease in wheat, caused by the viral pathogen Wheat streak mosaic virus (WSMV), and Fusarium wilt disease in banana, caused by the fungal pathogen Fusarium oxysporium f.sp. cubense (Foc). In this dissertation, I applied genomic and transcriptomic tools to study the Wsm2 locus that confers genetic resistance to WSMV. Analyzing exome and transcriptome reads from wheat lines carrying Wsm2, I characterized structural variations and identified unique transcripts specific to these Wsm2 carrying lines. Moreover, examination of candidate genes within the Wsm2 interval identified several tandemly duplicated candidate genes annotated as Bowman-Birk inhibitor (BBIs), which triggered my interests to perform a genome-wide characterization of this gene family in wheat. I studied the possible mechanisms behind its copy number and functional domain duplications and analyzed its diverse role in plant biotic and abiotic stress using wheat RNA-seq expression data. Finally, I analyzed a time course transcriptomic dataset from banana root infected with Foc subtropical race 4 strain (Foc-STR4). I used gene co-expression assembly network (WGCNA) to study host plant transcriptional response to Foc infection and analyzed the expression profiles of candidate genes underlying a novel locus conferring resistance to Foc-STR4 and prioritized candidates. In summary, this dissertation studied genetic variants underlying host genetic resistance to WSMV and Foc and shed light on plant defense mechanisms against these two important crop pathogens.
Zip file contains appendices.
Keywords: copy number variation; resistance gene; wheat streak mosaic virus; fusarium wilt; Bowman-Birk inhibitor; wheat